2014
DOI: 10.1186/2193-1801-3-93
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bolus injection of landiolol versus oral administration of propranolol before cardiac computed tomography

Abstract: Heart rate (HR) reduction is essential to achieve good image quality for cardiac computed tomography (CCT). We evaluated the efficacy of a bolus injection of landiolol, an ultra-short acting β-blocker, without the administration of oral β-blocker to reduce HR prior to CCT. We enrolled 678 consecutive patients who underwent CCT from December 2011 to March 2012 and divided them into three groups, which were a propranolol group (n = 277), a low-dose landiolol group (n = 188), and a high-dose landiolol group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…66 However, bradycardia was not reported in other studies that used landiolol injection of 0.125-0.5 mg/kg. 7,18,65,67 When continuous injection between 3 and 5 µg/kg/min was used to control the heart rate after cardiac surgery, ten of 68 patients experienced bradycardia (heart rate ,50 bpm), which recovered after cessation of drug infusion and administration of a cardiotonic agent.…”
Section: Bradycardiamentioning
confidence: 51%
See 3 more Smart Citations
“…66 However, bradycardia was not reported in other studies that used landiolol injection of 0.125-0.5 mg/kg. 7,18,65,67 When continuous injection between 3 and 5 µg/kg/min was used to control the heart rate after cardiac surgery, ten of 68 patients experienced bradycardia (heart rate ,50 bpm), which recovered after cessation of drug infusion and administration of a cardiotonic agent.…”
Section: Bradycardiamentioning
confidence: 51%
“…7,18,65,67 When continuous injection between 3 and 5 µg/kg/min was used to control the heart rate after cardiac surgery, ten of 68 patients experienced bradycardia (heart rate ,50 bpm), which recovered after cessation of drug infusion and administration of a cardiotonic agent. 15 Hypotension Hypotension is a rare side effect when a bolus injection of 0.125 mg/kg landiolol is used, 7,18,67 although Nakamura et al 66 reported hypotension (86/55 mmHg) in one out of 188 patients, which recovered after 10 minutes. Another study reported that one of 28 patients who received 0.25 mg/kg landiolol had mild hypotension, which resolved without any treatment.…”
Section: Bradycardiamentioning
confidence: 99%
See 2 more Smart Citations
“…If the HR remained > 60 beats/minute prior to the scan, 0.125 mg/kg of an ultrashort acting intravenous β-blocker (landiolol, Ono Pharmaceutical Co., LTD., Osaka, Japan) was administered to further reduce the HR. 20) Immediately before image acquisition, almost all patients received 0.3 mg nitroglycerin sublingual. Scan parameters were as follows: a collimation of 320 rows × 0.5 mm, rotation time of 350-400 ms, and tube voltage of 120 kV.…”
Section: Methodsmentioning
confidence: 99%